Development of Basic Mathematics Modules Based on Professional Competencies - Syelfia Dewimarni; Rizalina Rizalina; Deby Erdriani (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The low ability to understand mathematical concepts affects the learning outcomes of information systems study program students in basic mathematics courses. This is because basic mathematics courses tend to be disliked by the YPTK information systems study program students at Putra Indonesia University in Padang. After all, they consider basic mathematics courses do not significantly contribute to their field of expertise. Students prefer courses that suit their area of ​​expertise. Basic mathematics is an abstract subject and is a difficult subject. Students have difficulty applying mathematical concepts to solve problems. The learning module is a basic mathematics module based on professional competence. This basic mathematics module connects basic mathematics subject matter with subject matter in the field of expertise, namely information systems. This research aims to produce a basic mathematics module based on professional competence in the information systems study program at Putra Indonesia University YPTK Padang. This type of research is development research(R&D). The stages in developing this basic mathematics module are the development stages proposed by Plomp. This research carried out a preliminary research stage. Experts carry out product validation. Our instrument is a validation sheet with a Likert scale. The results of the expert validation analysis from aspects of presentation/dictates, suitability of content, language, and graphics obtained an average of 3.39 with a very valid category, which means that the basic mathematics module based on professional competence is suitable for use in basic subjects. Mathematics learning.